Empowering Young Voices: How 'Tubuhku Milikku' Increase Personal Safety Skills To Prevent Sexual Violence In Early Childhood - Fariha Husna Amalia; Berliana Widi Scarvanovi (Green Publisher, 2025)
Cases of sexual violence involving children occur frequently every year. This phenomenon highlights the importance of early sexual education to instill the ability to protect oneself from sexual abuse. Personal safety skills education teaches children to recognize, resist, and report behaviors or situations that may pose a threat, helping them stay safe in the future. One engaging approach to delivering sexual education is through the song “Tubuhku Milikku” or My Body Belongs to Me. This study employed a quasi-experimental method with a non-equivalent control group design. Participants were children aged 4 to 6 years who had never received sexual education before. The total sample consisted of 40 children, with 20 in the control group and 20 in the experimental group, selected using purposive sampling. Data were analyzed using the Mann-Whitney test, yielding a significance value of 0.000 (< 0.05), indicating the song “My Body Belongs to me” had a positive effect on improving personal safety skills. Additional analysis using the Wilcoxon test on pretest and posttest results showed a significance value of 0.950 (> 0.05) for the control group and 0.002 (< 0.05) for the experimental group, demonstrating that only the experimental group experienced an increase in personal safety skills.